Management of coastal wetlands as an effective climate response : lessons learned from global blue carbon projects to aid successful project implementation in South Africa - Brown, Louise (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPA)--Stellenbosch University, 2022.